Sekayam Subdistrict’s Food System Activities and Local Food Security - Purnawan, Endar; Brunori, Gianluca (Future Science / FSH-PH Publications, 2022)
This study analyzes Sekayam subdistrict’s local food system and local food security. Based on an analysis of local food vendor interviews, this research sheds light on the local food system based on five food groups modified from seven food groups of household dietary diversity scale measurement, according to the local condition. The stages of data analysis in this study adhered to the data analysis process modified from Neuman. The result indicates that the Sekayam subdistrict is self-sufficient in rice, vegetables, and freshwater fish but depends on other places for meat, seafood, and other foodstuffs such as cooking oil, milk, eggs, and sugar. Taken together, the research findings highlight the importance of developing some potential food sources to fulfill a community need so that Sekayam subdistrict in the future no longer depends much on other places supplied, to pursue better local self-sufficiency and better local food security. This paper strongly recommends policymakers, stakeholders, and local farmers, as well as the community, to plan and take some actions to pursue local self-sufficiency and better local food security in the future. The activity includes food production, processing and packaging, distribution and retailing, and consumption.